2023
DOI: 10.3389/fphar.2022.1010484
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous cinnamon extract ameliorates bowel dysfunction and enteric 5-HT synthesis in IBS rats

Abstract: Cinnamon protects against irritable bowel syndrome with diarrhea (IBS-D) in humans, but its efficacy and underlying mechanism of action remain poorly understood. Maternally separated (MS) IBS-D rat model and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced post-inflammatory IBS-D rat model are characterized by visceral hyperalgesia and diarrhea. This study used the two models to evaluate the effect of cinnamon extract (CE) on bowel symptoms. The MS rat model was also used to explore its underlying anti-IBS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Similar results have been observed for curcumin and many other natural products [21]. In another study, aqueous cinnamon extract (aCE) partially controlled bowel Khedkar and Khan BMC Complementary Medicine and Therapies (2024) 24:131 symptoms by downregulating tryptophan hydroxylase 1 in a model of irritable bowel syndrome [22]. It has also been reported that cinnamon extract acts as a proapoptotic agent, downregulating BCL2, BcL-xL and Survivin [15].…”
Section: Introductionsupporting
confidence: 62%
“…Similar results have been observed for curcumin and many other natural products [21]. In another study, aqueous cinnamon extract (aCE) partially controlled bowel Khedkar and Khan BMC Complementary Medicine and Therapies (2024) 24:131 symptoms by downregulating tryptophan hydroxylase 1 in a model of irritable bowel syndrome [22]. It has also been reported that cinnamon extract acts as a proapoptotic agent, downregulating BCL2, BcL-xL and Survivin [15].…”
Section: Introductionsupporting
confidence: 62%
“…The current treatment cannot meet the needs of IBS-D patients, so complementary and alternative medicine (CAM) provides pa-Am J Transl Res 2024; 16(3):781-793 tients with options [9]. Acupuncture, as a complementary and alternative therapy [10], has been practiced in China for thousands of years [11], and is becoming more popular and accepted among the public and health care professionals in the west. IBS is among 63 kinds of common diseases for which acupuncture was recommended by the World Health Organization (WHO) in 1996 [12].…”
Section: Introductionmentioning
confidence: 99%